Interprofessional Collaboration among Health Care Team Members in Critical Care Units: Highlighting the Professional Qualities - Al-Twigey, Maitham A.; AL-Fayyadh, Sadeq A. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Interprofessional collaboration (IPC) is the best way to provide high-quality and safe healthcare for the patient, reduce costs and length of hospital stay, as well as increase job satisfaction of the staff. However, many factors may hinder the achievement of interprofessional collaboration (IPC), and these need to be determined. Objective(s): Determining the national status of interprofessional team collaboration among healthcare team members, including nurses, physicians, and clinical pharmacists, in Critical Care Units, and examining the statistical difference between the professional qualities of the subjects and their levels of interprofessional team collaboration, are the goals of this study. Methods: A descriptive cross-sectional design was used in the present study. The current study was conducted in the Intensive Care Units (ICU) and Cardiac Care Units (CCU) of eight hospitals of the Najaf Governorate, in the Republic of Iraq. The 364 participants recruited in this study were healthcare team members, which included physicians, nurses, and pharmacists. The instrument used in the study is the Assessment of Interprofessional Team Collaboration Scale-II. Arithmetic means, frequencies, and percentages, as well as the Kruskal-Wallis and Mann-Whitney tests, were the statistical methods used in the study. Results: The level of interprofessional collaboration (IPC) was moderate among the physicians with a mean score (MS) of 3.25, and pharmacists with 2.55, while it was lower in nurses at 2.06. Of equal importance, significant mean differences were observed between the overall scores of Interprofessional Team Collaboration among the healthcare team members and their sexes, number of physicians, academic preparation, specialization, work shift, and educational level. Conclusion: The current study showed that Interprofessional Team Collaboration was not consistent with the standard expected level. Further, the professional qualities of many subjects exert significant effects on this level.